Perov’s theorem applied to systems of equations - Motronea, Gabriela; Otrocol, Diana; Rasa, Ioan (Modern Mathematical Methods, 2023)
In this paper, we consider systems of equations having a linear part and also a nonlinear part. We give sufficient conditions which imply the existence and uniqueness of solutions to the system. Using Perov's theorem, our results extend some results in the literature. An application using the iterative method, numerical experiments and graphics illustrate the main result.